2012
DOI: 10.1097/pai.0b013e3182434113
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GRP78 Is Associated With Malignant Transformation in Epithelial Ovarian Tumors

Abstract: The present study suggests that GRP78 plays a significant role in malignant transformation of epithelial ovarian tumors and may represent an important biomarker for EOCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…For example, GRP78, the most important marker of UPR, has been identified as a survival factor for rescuing cells from cell death and overexpression of GRP78 has been reported to be associated with poor prognosis in a number of malignant tumors (13,14). Nevertheless, the role of GRP78 in regulating the proliferation and growth of hypopharyngeal carcinoma cells under severe hypoxia remains to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GRP78, the most important marker of UPR, has been identified as a survival factor for rescuing cells from cell death and overexpression of GRP78 has been reported to be associated with poor prognosis in a number of malignant tumors (13,14). Nevertheless, the role of GRP78 in regulating the proliferation and growth of hypopharyngeal carcinoma cells under severe hypoxia remains to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
“…A key player in this process is the survival protein GRP78. GRP78 is overexpressed in many human cancers, where it mediates tumor growth by enhancing proliferation and protecting against apoptosis (16,21,41). Our findings of an increased expression of GRP78 not only in the human pancreatic cancer cell lines, but also in the human pancreatic cancer tissue samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although GRP78 expression is maintained at low basal levels in major adult organs, it has often been found to be upregulated in cancer cells (2,16,26,34,36). Studies have shown that although the majority of GRP78 resides in the ER lumen, a fraction of it exists as an ER transmembrane protein, with its NH 2 portion in the cytosol.…”
mentioning
confidence: 99%
“…Overexpression of GRP78 correlates with malignant transformation in epithelial ovarian tumor cells (19), while inducible knockout of GRP78 in the hematopoietic system suppresses Pten-null leukemogenesis (20). Mem GRP78 is associated with increased cancer stemness in head and neck cancer (21).…”
Section: Introductionmentioning
confidence: 99%